Associations of Synoptic Weather Conditions With Nocturnal Bird Migration Over the North Sea - Manola, Iris; Bradarić, Maja; Groenland, Rob; Fijn, Ruben; Bouten, Willem; Shamoun-Baranes, Judy (Frontiers in Ecology and Evolution, 2020)
The southern North Sea is part of an important flyway for nocturnal bird migration, but is also risky as it stretches over large surface of water. Selecting nights with suitable weather conditions for migration can be critical for a bird’s survival. The aim of this study is to unravel the weather-related bird migration decisions, by providing a descriptive analysis of the synoptic weather conditions over the North Sea on nights with very high and low migration intensities and compare these conditions to the prevailing climatology. For this study, bird radar data were utilized from an offshore wind farm off the Dutch coast, in the North Sea. The study suggests that atmospheric conditions clear of rain and frontal systems, dominated by high pressure systems and tailwinds in spring and sidewinds in autumn are most favoring for nights of intense migration. Differences in temperature, relative humidity and cloud cover appear less significant between intense and low migration nights, suggesting that these variables exert only a secondary role on migration. We discuss how future developments in radar aeroecology and the integration of meteorology can help improve our ability to forecast bird migration.